A versatile photothermal vaccine based on acid-responsive glyco-nanoplatform for synergistic therapy of cancer. (June 2021) - Gao, Yanan; Zhao, Qingyu; Xiao, Min; Huang, Xuefei; Wu, Xuanjun
Abstract: The race is on for therapeutic agents that stop cancer. An effective vaccine offers a safe and promising approach for cancer immunotherapy. However, substantial barriers to immunotherapy in cancer vaccines include the low immunogenicity of cancer antigens and the immunosuppression commonly present in solid tumors, resulting in significant challenges for developing a clinically effective cancer vaccine. Here, the state of the art of synergistic therapy, which includes the photothermal effect combined with immunotherapy, was investigated to target tumors. For the first time, indocyanine green (ICG, referred to as I), imiquimod (R837, referred to as R) and a foreign cytotoxic T lymphocyte antigen peptide (CTL-Ap, referred to as Ap) with the sequence of SIINFEKL from ovalbumin (OVA) were encapsulated by acetalated dextran (AcDEX) to form nanoparticles (NPs) averaging 92 nm in diameter as an immunogen. Administration of the resulting multifunctional vaccine I-R-Ap-AcDEX NPs enhanced antitumor cytotoxic T lymphocyte (CTL) immunotherapy. On the one hand, subcutaneous immunization of the NPs allows foreign Ap to enter the major histocompatibility complex class I (MHC-I) cross-presentation pathway of antigen-presenting cells, thereby presenting Ap and eliciting high levels of Ap-specific CTLs. On the other hand, intratumor/intravenous injections of the NPs allow foreign Ap to enter tumor cells and present Ap through the MHC-I cross-presentation pathway. Ap-specific CTLs can kill Ap-presented tumor cells. Furthermore, the NPs generated near-infrared laser triggered the photothermal killing of tumor cells. To our knowledge, this is the first report of AcDEX NPs in antitumor photothermal therapy. Strikingly, systemic administration of the I-R-Ap-AcDEX NPs combined with near-infrared laser irradiation allowed for complete protection to mice from the tumors when applied to two non-OVA tumor models. This quite impressive result displays the great promise of synergistic therapy by the vaccine I-R-Ap-AcDEX NPs, an approach that harnesses the photothermal effect to boost antitumor immunotherapy.